Maternal and Neonatal Markers of the Homocysteine Pathway and Fetal Growth: The Generation R Study. Issue 4 (July 2016) - Bergen, Nienke E.; Schalekamp‐Timmermans, Sarah; Jaddoe, Vincent W. V.; Hofman, Albert; Lindemans, Jan; Russcher, Henk; Tiemeier, Henning; Steegers‐Theunissen, Régine P. M.; Steegers, Eric A.P.
Abstract: Background: Suboptimal dietary intake during pregnancy may have long‐term health implications in children. These effects may be mediated by fetal growth. We investigated the associations of early pregnancy and umbilical cord total homocysteine (tHcy), folate, and total and active vitamin B12 concentrations with fetal growth parameters repeatedly measured in pregnancy and at birth. Methods: This study was performed in 5890 pregnant women, participating in a population‐based prospective cohort study. Blood samples were obtained from women in early pregnancy and from the umbilical vein at delivery. Fetal size parameters were repeatedly measured by ultrasound. Information about birth anthropometrics was retrieved from medical records. Results: High early pregnancy maternal tHcy (≥8.31 μmol/L), as compared with low maternal homocysteine (≤5.80 μmol/L), and low early pregnancy maternal folate (≤9.10 nmol/L), as compared with high maternal folate (≥25.81 nmol/L) concentrations, were associated with reduced weight growth patterns throughout pregnancy, resulting in birthweight differences of −102.3 g (95% CI −139.6, −65.0) and −113.0 g (95% CI −159.6, −66.3), respectively. Low umbilical cord folate concentrations (≤15.20 nmol/L) as compared with high umbilical cord folate concentrations (≥28.41 nmol/L) were also associated with a lower birthweight and birth length ( P  <   0.001). Interestingly, compared with higher umbilical cord vitamin B12, lower vitamin B12 concentrations were associated with a higher weight, length, and head circumference at birth ( P  <   0.01). Conclusion: Early pregnancy maternal and umbilical cord markers of the homocysteine pathway are significantly associated with fetal growth patterns. These differences arise from mid‐pregnancy onwards.